Reading the Signs of Ottoman/Istanbul Art Nouveau in the Buildings of Raimondo D’Aronco (Architecture Image Studies, 2025)
Ottoman architecture gained a new appearance under the influence of imported architectural styles throughout the eighteenth and nineteenth centuries. With the Palace opening out to the world at large, inviting western artists to the Empire, the western understanding of architecture began to reign over Ottoman concepts as all structures were now included in a new stylistic organization through the influence of foreign architects. In particular, with the era of Sultan Abdulhamid II (1876-1909), Ottoman architecture was impacted by the force of architectural movements originating in Europe that brought Neoclassicism, Neo-baroque, Neo-gothic, Orientalism, Art Nouveau, Eclecticism, Swiss Chalet, and the English Victoria and Art Deco styles to the foreside. The most influential of these movements in Ottoman society, however, was Art Nouveau. The most powerful representative of Art Nouveau in the Ottoman realm was Abdulhamid II’s architect, Raimondo D’Aronco. A “Palace” architect, it was thanks to D’Aronco that the Art Nouveau style came to influence Istanbul’s architectural traditions, and it was also through him that a new Ottoman/Istanbul Art Nouveau with a “local” character was born. The aim of this paper is to explore the Art Nouveau style that has held sway over Ottoman architecture since 1893 through the works of its most famous implementer, Raimondo D’Aronco, and to define the characteristics of the Ottoman/Istanbul Art Nouveau that made his designs so notable. Toward this aim, some of the architect’s works have been selected and analyzed as to plan, construction system and decorative elements.